The effectiveness of flipped classroom based blended learning on students critical thinking skills - Luciana, Occe; Rahayu, Widya Andayani; Normansyah, Normansyah; Suyahman, Suyahman; Rusmawan, Rusmawan; Manahor, Anwar (Psychology, Evaluation, and Technology in Educational Research, 2024)
This study aims to determine the effectiveness of flipped classroom-based blended learning on students' critical thinking skills. This study is a type of meta-analysis research. Data sources come from 14 national and international journals published in 2018-2023. The process of finding data sources comes from Google Scholar, ERIC, DOAJ, EBSCO, ProQuest, ScienceDirect and PLoS ONE. Keywords search for blended learning data, blended learning based on flipped classroom, and the effectiveness of blended learning based on flipped classroom on students' critical thinking skills. Data analysis techniques with the help of JSAP applications. The results of the study concluded that the average value of effect size (ES = 0.838) high sizeeffect category and standard error of 0.109 . These findings explain that the flipped classroom-based blended learning model has a positive influence on students' critical thinking skills.